Investigation of tribological characteristics of nickel alloy-based solid-lubricating composites at elevated temperatures under vacuum - Jinming Zhen; Jun Cheng; Hui Tan; Qichun Sun; Shengyu Zhu; Jun Yang; Weimin Liu (Friction)
Abstract The development of a high-performance solid-lubricating composite with excellent self-lubricity over a broad temperature range in vacuum is significant to solve the frictional problems of spatial mechanisms. In this study, the vacuum tribological behaviors of nickel-matrix/Ag/(Ca, Ba)F2/graphite (0–2 wt%) composites were studied from 25 to 800 °C. The results show that the synergistic effects of solid lubricants can significantly improve the tribological properties of the composites in vacuum, with the graphite content contributing considerably. For 2 wt% graphite, a low friction coefficient (0.14–0.25) and the lowest wear rate ((0.12−4.78)×10−5 mm3·N−1·m−1) were observed in vacuum over the entire testing temperature range. Moreover, the wear mechanisms were clarified via analysis of the chemical composition and morphologies of the sliding surfaces.